2017
DOI: 10.5194/esd-8-719-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of land surface humidity between observations and CMIP5 models

Abstract: Abstract.We compare the latest observational land surface humidity dataset, HadISDH, with the latest generation of climate models extracted from the CMIP5 archive and the ERA-Interim reanalysis over the period 1973 to present. The globally averaged behaviour of HadISDH and ERA-Interim are very similar in both humidity measures and air temperature, on decadal and interannual timescales.The global average relative humidity shows a gradual increase from 1973 to 2000, followed by a steep decline in recent years. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…Climate models may have considerable biases in simulating RH (Dunn et al, ), which could potentially undermine the reliability of detection and attribution analyses of RH‐related variables. Nevertheless, our study shows that the observed WBGT trend is well within the range of modeled WBGT trend across the land area with adequate observations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Climate models may have considerable biases in simulating RH (Dunn et al, ), which could potentially undermine the reliability of detection and attribution analyses of RH‐related variables. Nevertheless, our study shows that the observed WBGT trend is well within the range of modeled WBGT trend across the land area with adequate observations.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Post-AR5 studies (Douville and Plazzotta, 2017;Dunn et al, 2017) suggest that the apparent decrease in land surface RH was underestimated by most models from the fifth phase of the Coupled Model Intercomparison Project (CMIP5). This observed drying was attributed to anthropogenic forcings and used to constrain the projected decline of near surface RH over the boreal summer mid-latitude continents, suggesting a systematic underestimation of the land surface drying by these models (Douville and Plazzotta, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Energy-added treatments represented realistic potential future warming (projected 5.9°C increase) expected for the SPRUCE site in the year 2085. The treatments had a less distinct match to potential changes in average relative humidity (projected 3 percentage-point increase), although average moisture changes are also expected to be accompanied by a larger range of variability at the northern Minnesota SPRUCE site based on comparison to forecast data (IPCC, 2014;Dunn et al, 2017). (A, B, C) are the estimated incremental effect of a 1°C increase in warming on the mean annual biomass growth rate, and shaded areas around lines are 95% confidence intervals of the estimated mean.…”
Section: Resultsmentioning
confidence: 99%
“…RH ( experiment was accompanied by proportional decreases in relative humidity as a product of the experimental design (Hanson et al, 2017), including a reduction in the potential for dew formation. Moisture reductions ranging from mild to drastic are projected for the Midwest region of the United States given plausible carbon emissions and atmospheric scenarios (Dunn et al, 2017), which could severely impact photosynthesis and biomass accumulation of poikilohydric epiphytes that rely on dew and humid air as sources of moisture instead of liquid rain (Lange et al, 2007;Gauslaa, 2014). Dew occurs at relative humidity approaching 100% and can thus be viewed as one point along an atmospheric moisture continuum (humid air < dew < liquid rain).…”
Section: Mat (°C)mentioning
confidence: 99%